THE DEFINITION OF EQUIVALENCE (SOLAR) TEMPERATURE IN CALCULATING HEAT GAIN VIA OPAQUE FENCING STRUCTURES - and (Municipal economy of cities. Series: «Economy science», 2013)
The article is about calculation of the heat flux that enters the room from the sun. The expediency of using the so-called equivalent (solar) temperature in the calculations of heat gain through the all kinds of opaque building envelopes was critically reviewed. The heat balance of the walling external surface was considered in detail. The recommendations of using equivalent temperature were also given.